A DFT Study of Collector Adsorption on the Sulphide Mineral Surface in the Presence of Water Molecules - Jianhua Chen; Xianhao Long; Ye Chen; Zhenghe Xu; Qingxia Liu (Canadian Institute of Mining, Metallurgy and Petroleum, 2016)
"It is crucial to understand the mechanism of the collector interacting with the mineral surface in the presence of water molecules, which could influence the relaxation and electronic properties of sulphide mineral surface due to the proximity effect for narrow band gap of semiconductors. The adsorptions of three typical collector molecules (xanthate, dithiocarbamate and dithiophosphate) on the sulphide mineral surfaces in the absence and presence of water molecule have been simulated by density-functional theory (DFT). The calculated results show that the adsorptions of collectors on clean mineral surface in vacuum are not in agreement with the observed flotation behaviours. The presence of water molecules has a great influence on the adsorption of collectors. The analysis of density of states of the mineral surface atom suggests that the adsorption of water molecules could influence the electronic properties of mineral surface and consequently influence the adsorption between the surface and the collector molecule.INTRODUCTIONIn the separation of multi-metal sulphide ores, the selectivity of a collector is a key factor for the efficient recovery of the aimed mineral. Xanthate, dithiocarbamate (DTC) and dithiophosphate (DTP) are the most common collectors used in the flotation of sulfide minerals. Generally, xanthate exhibits powerful collecting property but lack of selectivity. While dithiophosphate and dithiocarbamate show the good selectivity in the lead and copper sulphide mineral flotation. The mechanisms of these collectors interacting with the sulphide mineral had been attracted many attentions and several mechanism based on experimental results had been reported (Chander & Fuerstenau, 1974; Fuerstenau, 1990; Raju & Forsling, 1991; Crozier, 1991; Bradshaw, Cruywagen & O’Connor, 1995; Guler, Hicyilmaz, Gokagac & Emekci, 2006). However, the micro-mechanisms of the selectivity of these three thiol collectors on different sulphide mineral surfaces are not fully understood."